(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the issues of integrating physical education and sport-related health-enhancing means in athletic gymnastics from both scientific-theoretical and practical perspectives. The study analyzes the health-improving, developmental, and preventive potential of athletic gymnastics and substantiates effective ways of using sport and health-enhancing tools in the process of physical education classes. It is shown that integrated training sessions make it possible not only to develop muscular strength, endurance, flexibility, and motor coordination, but also to improve the functional state of the cardiovascular and respiratory systems.